Linguistic Characteristics and Psychological Features of Speech Activity Products of Students with Second Signaling System Domination - M A Mirchetich; N A Fomina (Peoples' Friendship University of Russia (RUDN University), 2014)
The paper presents the multilevel, complex research results of the texts as products of individual speech activity of the students with the second signaling system domination, which allows to estimate the personality features of the students by means of their speech.